Paclitaxel Induces Axonal Degeneration and Alters Cold Temperature Sensitivity in Adult Rats - Michalová, Zuzana; Vanický, Ivo (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):291